Efek Metode Non Farmakologik terhadap Intensitas Nyeri Ibu Bersalin Kala I - Marwati Biswan; Henny Novita; Masita Masita (Politeknik Kesehatan Tanjung Karang, 2017)
Pain is one of the processes during the labor, the pain during the labor is able to increase the blood pressure, the fetal heart rate also increased and the focus of mothers during the childbirth is disturbed. According to data research shown that 60% primipara describes the pain caused by huge contraction, 30% about medium. In multipara, 45% feel a huge pain, 30% is medium and the lower about 25%. The purpose of this research is to understand the effectivity of the proper way to the non-pharmacological pain management for the phase 1. This research used a quasi-experimental design with the pre-post test without control group design methods. The population used in this research is maternal with phase 1 on an active postpartum. The gaining of a sample using a quota sampling technic consists of 60 maternal who were divided into two groups of 30 respondents per each. The results obtained in this research given the average degree of pain after the relaxation techniques and massage. (The group I) is 5, 47 with the result of p=0.001. The average degree of pain result after having a warm and cold compress for (the group II) is 6,60 ± 1,003 with the result of p=0.000. The conclusions of the research are there are effects in an adduction of deep breathing relaxation technique such of: the back massage, cold and warm compresses toward the decreasing of pain for phase 1 active labor. The deep breath relaxation method and back massage are more effective than cold and warm compresses in relieving pain intensity for the maternal.